An Aesthetic View on Rouzbehan Baghli’s Prose in Praising Prophet Muhammad (PBUH) - Karim Shahsavan; Abdollah Hasanzadeh Mirali; Davood Mohammadi; S.Hasan Tabatabaei (مطالعات زبانی و بلاغی)
Mystic prose is poetic artistic prose and what makes it stand out is the use of literary structures and poetic elements. Mystics offer religious and spiritual concepts in a beautifully shaped format, which is rich in language and prose. The aforementioned features have kept this type of prose from obsolescence and difficulty. For this reason, mystic prose has been in the center of attention for centuries and has many readers, just like rich poetry. Thanks to mystics like Eynolghozat Hamedani, Suhrawardi, and Rouzbehan Baghli, the sixth-century prose has always been at the highest level of lingual and literary aesthetics. This type of prose illustrates healthiness, rigor, delicateness, freshness, and whatever is expected from distinguished mystic prose. In this study, an attempt was made to analyze the metaphoric language of Rouzbehan Baghli in praising Prophet Muhammad (PBUH). We tried to scrutinize his innovation, which is the use of different stylistic devices and structures in the context of metaphors. Also, we hope to illustrate his other innovations in enchanting the audience with mystic prose.